Proceso de atención en enfermería en paciente de 29 años colecistectomizado. - Ibarra Vásquez, Emelyn Margarita (2022)
Gallstones were the main cause of morbidity with 43,673 discharged from hospitals (INEC, 2019). The clinical case is of a 29-year-old female patient who came to the Alfredo Noboa Montenegro Hospital for outpatient consultation due to colic-type abdominal pain in the right hypochondrium of intensity 8/10 according to the VAS scale, positive Murphy sign. Accompanied by nausea that reaches vomiting, algic fasciae are evident, plus quantified thermo fever. Laboratory tests are performed where neutrophilia without leukocytosis is evidenced, an abdominal echo is performed in the liver and bile ducts, where a thickening of the wall is found in the gallbladder, size 5.72 x 3.42cm, with abundant hyperechoic images ( more than 7) being the one with the largest diameter of approximately 2cm and giving a posterior shadow, with a diagnosis of cholelithiasis, whereby the treating doctor assesses and schedules a surgical procedure by nursing. The anamnesis is carried out where it is stated that she has a surgical history with an abdominoplasty 7 years ago, gynecological history G 1, C1, personal history of hypertensive mother, diagnosis of patients is taken to the surgery service by outpatient staff, negative COVID test, with pre-anesthetic visit.